2021
DOI: 10.4103/jomfp.jomfp_68_21
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic index, facial index and dental parameters: A correlative study to evaluate their significance in facial reconstruction

Abstract: Background: It becomes extremely challenging for forensic artists to reconstruct the highly decomposed faces, especially during mass disasters. It would be of great help for the identifying team of experts if there was a method to determine the facial and cephalic dimensions. This study aims to provide a method to generate a simplified method to calculate the facial and cephalic indices of an individual based on the dentition since human dentition remains almost intact in most scenarios. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Regarding other studies, which analysed anthropometric characteristics in the facial and cranial area, our study differs from others mainly because the facial and cephalic characteristics were analysed individually to demonstrate the existence of a relation between both variables. In addition, sample variation can be directly associated to miscegenation between native people and colonists during the 18th century, which differs from the following studies: Khatun's study showed that the prevailing characteristic was dolichocephalic (Khatun, 2018); in the study of Muralidhar et al (2021), dolichocephalic was the prevailing FI characteristic, and Koizumi et al (2010) showed that brachycephalic was the prevailing characteristic of its population. It should be noted that all these studies had samples of Japanese or pure indigenous ancestry.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Regarding other studies, which analysed anthropometric characteristics in the facial and cranial area, our study differs from others mainly because the facial and cephalic characteristics were analysed individually to demonstrate the existence of a relation between both variables. In addition, sample variation can be directly associated to miscegenation between native people and colonists during the 18th century, which differs from the following studies: Khatun's study showed that the prevailing characteristic was dolichocephalic (Khatun, 2018); in the study of Muralidhar et al (2021), dolichocephalic was the prevailing FI characteristic, and Koizumi et al (2010) showed that brachycephalic was the prevailing characteristic of its population. It should be noted that all these studies had samples of Japanese or pure indigenous ancestry.…”
Section: Discussionmentioning
confidence: 73%
“…It should be noted that all these studies had samples of Japanese or pure indigenous ancestry. In the study of Muralidhar et al (2021), leptoprosopic was the prevailing characteristic for FI. In del Sol (2006) study, concluded that the total mean FI had mesoprosopic characteristics with a tendency towards euryprosopic.…”
Section: Discussionmentioning
confidence: 99%
“…To a large extent, frontal and facial indices are necessary considerations in aesthetics and reconstructive facial surgeries [20,25]. Although the concept of beauty may appear subjective, it is enshrined on some anatomical basis [26].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this classification has long been questioned. In a study by Muralidhar et al [ 35 ], correlations between the cephalic index, the facial index and the interincisal distance were found. In this respect, a correlation between the cephalic index and our clusters could be investigated in a further study.…”
Section: Discussionmentioning
confidence: 99%